Longitudinal Emergency Medical Technician Attributes and Demographic Study (LEADS) Design and Methodology. (28th November 2016) - Levine, Roger
Abstract: Objectives: The objective of this study is to describe the Longitudinal Emergency Medical Technician (EMT) Attributes and Demographic Study (LEADS) design, instrument development, pilot testing, sampling procedures, and data collection methodology. Response rates are provided, along with results of follow-up surveys of non-responders (NRs) and a special survey of Emergency Medical Services (EMS) professionals who were not nationally certified. Methods: Annual surveys from 1999 to 2008 were mailed out to a random, stratified sample of nationally registered EMT-Basics and Paramedics. Survey weights were developed to reflect each respondent's probability of selection. A special survey of NRs was mailed out to individuals who did not respond to the annual survey to estimate the probable extent and direction of response bias. Individuals who indicated they were no longer in the profession were mailed a special exit survey to determine their reasons for leaving EMS. Results: Given the large number of comparisons between NR and regular (annual) survey respondents, it is not surprising that some statistically significant differences were found. In general, there were few differences. However, NRs tended to report higher annual EMS incomes, were younger, healthier, more physically fit, and were more likely to report that they were not practicing EMS. Comparisons of the nationally certified EMS professionals with EMS professionals who were not nationally certified indicated that nationally certified EMS providers were younger, had less EMS experiences, earned less, were more likely to be female and work for private EMS services, and less likely to work for fire-based services. These differences may reflect state and local policy and practice, since many states and local agencies do not require maintenance of national certification as a requirement to practice. When these differences were controlled for statistically, there were few systematic differences between non-nationally certified and nationally certified EMS professionals. Conclusions: The LEADS study is the only national, randomized, and longitudinal data source for studying EMS professionals in the United States. Although not without flaws, this study remains an excellent source of information about EMS provider demographics, attributes, attitudes, workplace issues and concerns, and how the profession has changed from 1999 to 2008. R Levine .Longitudinal Emergency Medical Technician Attributes and Demographic Study (LEADS) design and methodology .Prehosp Disaster Med .2016 ;31 (Suppl.1 ):s7 –s17 .